2000
DOI: 10.3758/bf03200270
|View full text |Cite
|
Sign up to set email alerts
|

Place and cue learning in turtles

Abstract: Turtles (Pseudemys scripta) were trained in place, cue, and control arm maze procedures, The turtles learned both tasks with accuracy, Subsequent probe and transfer trials revealed guidance and mapping strategies by the cue and the place groups, respectively. Thus, the turtles in the cue procedure solved their task by directly approaching the single individual intramaze cue associated with the goal, whereas the animals in the place task seemed to be using a maplike representation based on the encoding of simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 88 publications
(74 reference statements)
4
50
0
Order By: Relevance
“…One important property of cognitive mapping-based navigation is that, as cognitive maps store redundant environmental information, when a subset of spatial cues become unavailable, accurate navigation is still possible on the basis of those that remain [O'Keefe and Nadel, 1978]. The performance of turtles and goldfish trained in place tasks agrees with this requirement: it is not impaired by the removal or occlusion of any one of the component elements of the landmark array, indicating that none of those cues is essential by itself to locate the goal [Rodríguez et al, 1994;Ló pez et al, 1999Ló pez et al, , 2000cLó pez et al, , 2001Stone et al, 2000] (fig. 2D).…”
Section: Map-like Memory Representations Of Allocentric Space In Vertsupporting
confidence: 49%
See 1 more Smart Citation
“…One important property of cognitive mapping-based navigation is that, as cognitive maps store redundant environmental information, when a subset of spatial cues become unavailable, accurate navigation is still possible on the basis of those that remain [O'Keefe and Nadel, 1978]. The performance of turtles and goldfish trained in place tasks agrees with this requirement: it is not impaired by the removal or occlusion of any one of the component elements of the landmark array, indicating that none of those cues is essential by itself to locate the goal [Rodríguez et al, 1994;Ló pez et al, 1999Ló pez et al, , 2000cLó pez et al, , 2001Stone et al, 2000] (fig. 2D).…”
Section: Map-like Memory Representations Of Allocentric Space In Vertsupporting
confidence: 49%
“…These studies demonstrate that, like mammals and birds, turtles and goldfish can navigate accurately and flexibly to a goal on the basis of information provided by an array of landmarks, by means of encoding their spatial relationships in a maplike representation that provides a stable frame of reference [Rodríguez et al, 1994;Holtzman et al, 1999;Ló pez et al, 1999Ló pez et al, , 2000c (fig. 2, 3).…”
Section: Map-like Memory Representations Of Allocentric Space In Vertmentioning
confidence: 99%
“…The use of visual cues to find a specific target has been demonstrated in numerous organisms including insects (Chittka, Geiger, and Kunze, 1995), turtles (Lopez et al, 2000), fish (Sovrano, Bisazza, and Vallortigara, 2003), rats ( Suzuki, Augerinos, and Black, 1980), birds (Cheng, 1989), non-human primates ( Sutton, Olthof, and Roberts, 2000) and humans ( Spetch, 1995). These studies have revealed several ways in which spatial information from visual cues near a target may be encoded and used to remember the target location.…”
Section: Introductionmentioning
confidence: 99%
“…a prominent tree acting as a landmark) results in inability to access remembered resources even when close to them (e.g. López et al 2001). A more complex but flexible system is the use of a cognitive map in which the goal is defined by its spatial relation to a number of landmarks (O'Keefe and Nadel 1978), thus the loss of a single landmark does not alter success; however, the loss of multiple cues in a disrupted habitat could result in an animal failing to return successfully to a resource.…”
Section: Introductionmentioning
confidence: 99%
“…A simple but effective strategy is the use of a distinctive cue located near the goal (e.g. López et al 2001). This is then used as a beacon upon which an animal can home.…”
Section: Introductionmentioning
confidence: 99%